2017
DOI: 10.1159/000480664
|View full text |Cite
|
Sign up to set email alerts
|

Significant Hemorrhage Rate Reduction after Gamma Knife Radiosurgery in Symptomatic Cavernous Malformations: Long-Term Outcome in 95 Case Series and Literature Review

Abstract: Background: The natural history of cavernous malformations (CMs) has remained unclear. This lack of knowledge has made treatment decisions difficult. Indeed, the use of stereotactic radiosurgery is nowadays controversial. The purpose of this paper is to throw light on the effectiveness of Gamma Knife radiosurgery (GKRS) therapy. Methods: The authors reviewed data collected from a prospectively maintained database. A total of 95 patients (57 female and 38 male) underwent GKRS for high-surgical-risk CMs. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Alternative therapeutic strategies are considered when there is excessive risk of surgical complications. In this context, SRS has emerged as a viable treatment alternative for selected patients with CCMs [17,[31][32][33][34]. Given the hazards of rebleeding from a CCM with previous hemorrhage history, a more active approach with radiosurgical management of surgically inaccessible deep-seated CCMs has been suggested in the literature [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Alternative therapeutic strategies are considered when there is excessive risk of surgical complications. In this context, SRS has emerged as a viable treatment alternative for selected patients with CCMs [17,[31][32][33][34]. Given the hazards of rebleeding from a CCM with previous hemorrhage history, a more active approach with radiosurgical management of surgically inaccessible deep-seated CCMs has been suggested in the literature [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Pollock et al [40] 18 Gy, Kondziolka et al [65], and Liscak et al [66] applied a marginal dose of 16 Gy and tried to reduce ARE. Azimi et al [67], and Park and Hwang [68] prescribed a low marginal dose of 13 Gy on average (Table 2) [19,22,29,40,[66][67][68][69][70][71][72]. In 2019, Lunsford et al [32] wrote that the median radiation dose to the CM margin was 13 Gy to reduce hemorrhagic risk and radiation-induced complications.…”
Section: Dose Plan and Irradiation In Gamma Knife Radiosurgerymentioning
confidence: 99%
“…[ 41 ] A recent meta-analysis on gamma knife radiosurgery for CMs demonstrated effectiveness at preventing hemorrhage in the first 2 years following radiosurgery as well as afterward. [ 42 ] Although multiple recent studies have shown promising radiosurgery outcomes for CM,[ 43 44 ] limited data exist on the use of radiosurgery in pediatric patients as well as long-term outcomes. Given that transient postradiation associated changes such as perilesional edema are present in 25% of patients, and up to 10% of patients have permanent complications, radiation is not a widely recommended treatment for CMs.…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…[ 1 ] Indeed, in patients treated with stereotactic radiosurgery, hemorrhage-free survival is markedly better in children compared to adults. [ 44 ] In patients treated with surgery, earlier age at presentation was highly associated with favorable 1-year outcome. [ 18 ] Our pooled analysis revealed that 85.2% of patients who had epilepsy were Engel Class 1 after surgery.…”
Section: Prognosis and Outcomesmentioning
confidence: 99%